Long-term protection at 20-31 years after primary vaccination with plasma-derived hepatitis B vaccine in a Chinese rural community - Jing-Chen Ma; Zhi-Wei Wu; Hai-Song Zhou; Zhao Gao; Zhi-Yong Hao; Fei Jin; Yan-Hong Zhang; Min-Jie Li; Feng Wang; Qi Li; Sheng-Li Bi; Yu-Liang Zhao (Taylor & Francis Group, 2020)
Background: To assess the long-term protection conferred by plasma-derived hepatitis B vaccine at 20-31y after primary immunization during infancy in Chinese rural community. Method: Participants born between 1986 and 1996, who received a full course of primary vaccination with plasma-derived hepatitis B vaccine and had no experience with booster vaccination were enrolled. An epidemiological investigation was performed, and blood samples were collected to detect hepatitis B surface antigen (HBsAg), hepatitis B surface antibody (anti-HBs), and hepatitis B core antibody (anti-HBc). The positive rate of HBsAg, anti-HBs, and anti-HBc were calculated to evaluate the long-term protection of the plasma-derived hepatitis B vaccine. Results: A total of 949 participants were enrolled in the final analysis. Six subjects were detected to be HBsAg-positive, resulting in a HBsAg carrier rate of 0.63% (6/949). A total of 468 (52.41%) participants maintained a level of anti-HBs antibody ≥10 mIU/mL, with a GMC of 112.20 mIU/mL (95%CI: 97.72 ~ 128.82 mIU/mL). A significant downtrend was observed in the anti-HBs positive rate (P < .001). The average anti-HBc positive rate was 5.90% (56/949), increased with prolongation of immunization (P < .001). Conclusions: The plasma-derived hepatitis B vaccine maintained satisfactory protection at 20-31 y after primary immunization. These results indicate that a booster dose is not necessary. Further studies on the immune memory induced by the plasma-derived hepatitis B vaccine are needed.